IMPLEMENTASI DECISION SUPPORT SYSTEM SELEKSI PENERIMAAN PEGAWAI BARU PADA CV. CIPTA TOTALINDO PRIMA - Ofah Musyarrofah (Journal of Innovation And Future Technology (IFTECH), 2019)
Employees is an important factor in a company, because of the qualified employees, the company productivity will surely remain stable and growing. In fact, many companies give less attention to these important things. It can be proved on recruitment of new employees in CTP company which is still subjective assessment on this process Decision Support System Acceptance employee is a system that is able to improve the effectiveness and efficiency of management, increasing the speed and the validity of decisions relating to operational activities, and improve the quality of human resources of prospective employees. This paper discusses the decision support systems recruitment and placement of employees in the department are available based on the results of the selection and criteria - criteria that have been determined using the Fuzzy Logic. This method was chosen because it is able to provide an overview of decision support in the recruitment and placement department. Based on test results, a system built to help parts of the field of administration and finance to provide a snapshot in conducting the screening recruitment and placement department with a more precise and efficient.